Effects of posterior intrusion using skeletal anchorage on treating anterior open bite: A systematic review and meta-analysis - Maryam Omidkhoda; Erfan Bardideh; Arezoo Jahanbin; Milad Zarei (Tabriz University of Medical Sciences, 2023)
Background. Posterior intrusion with skeletal anchorage is one of the effective methods in the treatment of anterior open bite. Knowing the effects of posterior intrusion, the amount of possible molar intrusion using skeletal anchorage, and its impact on clinical and cephalometric indicators can help the clinician choose the optimal treatment method, especially in borderline surgical cases. Methods. In this systematic review, a series of articles were collected through a systematic search in databases, and the titles and summaries of all these articles were reviewed. After removing the irrelevant articles, the full texts of the related articles were read carefully, and their validity was evaluated. Only RCTs and observational studies that complied with PICO questions were included. The Cochrane Risk of Bias 2.0 (RoB 2), ROBINS-I, and GRADE were used to assess the risk of bias in the included studies. The relevant information on selected articles was extracted, and a meta-analysis was performed with Review Manager 5.4 software. Results. The meta-analysis revealed a significant average molar intrusion of 2.89 mm using temporary anchorage devices (TADs). A subgroup analysis showed that miniplates achieved greater intrusion (3.29 mm) compared to miniscrews (2.25 mm) (P=0.03). The level of applied force did not significantly affect the degree of intrusion. Dental parameters such as overbite and overjet were notably altered, with overbite increasing by 4.81 mm and overjet decreasing by 2.06 mm on average. As for the skeletal cephalometric characteristics, SNB, ANB, and SN-Pog increased while mandibular plane angle and lower anterior facial height (LAFH) decreased, and these changes were significant. Meanwhile, SNA and palatal angle changes were not significant. Conclusion. TADs have proved effective in achieving significant intrusion of maxillary molars, leading to marked improvements in dental and skeletal characteristics in patients with open bite malocclusion. Miniplates proved more effective in achieving greater intrusion.